Working in community services : management and practice - Wearing, Michael. (Allen and Unwin, 1998)
Community services. Social theory and welfare practice. The construction of clienthood. Administration and agency work. Supervision and work identity. Making client identities. The client's experience of service. Facing up to diversity and inequality.